Effects of orthokeratology lenses on choroidal thickness and choriocapillaris perfusion in myopic children - Wang, Lulu; Liu, Yu; Ma, Mengyao; Zhao, Yifan; Bao, Xiuli (Frontiers in Medicine, 2025)
PurposeTo investigate changes in subfoveal choroidal thickness (SFChT) and choriocapillaris (CC) perfusion in children wearing orthokeratology (Ortho-K) lenses.MethodsThis retrospective study included 61 myopic children, who were divided into two groups. The Ortho-K group wore Ortho-K lenses, while the control group wore single-vision distance spectacles. The SFChT, CC area and ocular parameters were measured before and after 1 week, 1 month, 3 months, and 6 months of treatment.ResultsIn the Ortho-K group, the SFChT significantly increased by 18.23 ± 11.35 μm. The CC area significantly increased by 0.39 ± 0.11 mm2 from baseline at the 1-week visit and continued to increase at the 1-month, 3-month, and 6-month follow-ups. In the control group, the choroidal parameters did not change significantly at 1 week. At the 1-, 3-, and 6-month follow-ups, the control group showed a notable reduction in SFChT and CC areas (p < 0.001). At the 6-month follow-up, there was a significant relationship between changes in SFChT and CC areas in the Ortho-K group (r = 0.890, p < 0.001). The increasing SFChT and CC areas were negatively correlated with AL (r = −0.827, p < 0.001; r = −0.717, p < 0.001), weakly negatively correlated with changes in VCD (r = −0.033, p < 0.05; r = −0.039, p < 0.05), and negatively correlated with K1 and K2 (r = −0.430, p < 0.001 and r = −0.545, p < 0.001, respectively; r = −0.417, p < 0.001 and r = −0.464, p < 0.001, respectively).ConclusionOrthokeratology notably increases SFChT and improves CC perfusion. Changes in choroidal thickness are linked to alterations in choriocapillaris perfusion. These effects are associated with the effect of orthokeratology in slowing axial length elongation.